Data Driven Inertia Distribution Index Monitoring Using Dynamic Mode Decomposition - K. K Thoufeer; Manas Kumar Jena (IEEE Access)
The integration of inertia-less renewable energy sources reduces the overall system inertia and leads to an uneven inertia distribution, which can significantly impact system stability. Uneven inertia distribution amplifies localized oscillations relative to the center of inertia oscillation, making it necessary to assess inertia distribution accurately. This article proposes a novel approach for estimating the inertia distribution of a power system from bus frequency measurements using higher-order dynamic mode decomposition. The proposed methodology identifies major oscillatory modes in the system and quantifies their spatial distribution to provide insights into inertia distribution across the system. The effectiveness of the approach is tested and validated on two different test systems: the IEEE 39-bus system and the Northern Region Power Grid of India. Simulation results demonstrate that the proposed method effectively estimates the inertia distribution, providing valuable information for stability assessment and control in modern power grids.